Managerial Capabilities in Peruvian Family Companies: An Exploratory Study - Salomon, Jaime O. (Pontificia Universidad Católica del Perú. CENTRUM, 2009)
In this research study, an attempt will be made to identify the managerial capabilities which determine performance of family firms in the context of the wheat milling industry in Peru. Researchers have suggested that the abilities and knowledge of the CEO, as applied to the organization, as well as the sort of social relationships (social capital) and the ability to envision the future (cognitive capital), are all relevant elements that contribute to shaping managerial capabilities. A qualitative methodology, focused on multiple cases studies, will be used. In-depth interviews for data collection will be held and a narrative (discursive) analysis will be done.
Keywords: Family-firm performance; Managerial capabilities; https://purl.org/pe-repo/ocde/ford#5.02.04